Research Gap on Differentiated Learning in The EFL Classroom: A Conceptual Framework - Mahmud, Adi F.; Idul, Muhammad; Sarmadani, Sarmadani (Journal of Language Learning and Assessment, 2024)
PurposeDifferential learning emerged as a solution to address the limitations of uniform learning approaches and the diverse characteristics present in the classroom, such as group heterogeneity, cultural diversity, background, language, and individual uniqueness. This study aims to: (1) analyses how Tomlinson, scholars, and researchers have applied differential learning in online articles and books; (2) identify the gaps in the implementation of differential learning in the EFL classroom; and (3) produce a conceptual framework for differentiated learning in the EFL classroom. MethodologyThe qualitative approach employing content analysis design is utilized to scrutinize articles and books that have been published online via Google Scholar, Crossref, and Scopus indexing, using the published and Perish 8 programs. The following articles and books are analyzed with three rare ones adopted by Siyoto & Sodik, (2015), namely: (1) information reduction entails condensing, selecting the most salient elements, prioritizing significant aspects, identifying key subjects and patterns, and eliminating superfluous content; (2) drawing inferences based on the acquired information; and (3) deriving conclusions pertaining to strategies that can effectively address the specific intricacies of the situation. Results/FindingsThe results of the research show that there are three research gaps that need to be followed up on from the implementation of differential learning in the EFL classroom: (1) the theoretical gap, (2) the practical knowledge gap, and (3) the methodological gaps. ImplicationsThe study not only reviews existing literature but also aims to fill critical gaps in understanding and application through the proposed conceptual framework, thereby advancing research and practice in this area.